Changes in plasma leptin concentration during different types of exercises performed by horses - W. Kędzierski (Animal, 2014)
Leptin is a tissue-derivative adipokine that regulates appetite, food intake and energy expenditure. It is still not clear how exercise affects plasma leptin concentration in horses. The aim of this study was to evaluate the influence of exercise intensity and duration on plasma leptin levels in working horses. A total of 38 horses were prospectively included in the study and grouped according to the type of exercise they performed: dressage (six stallions, group D), jumping (12 stallions, group J), race (12 Thoroughbred horses, six stallions and six mares, group R) and harness (10 light draft stallions, group H). Blood samples were taken both before and after routine exercise (immediately after the exercise, 30 min and 24 h after). Blood lactic acid (LA) and plasma concentration of leptin, cortisol, uric acid, triacylglycerols, glycerol and free fatty acids were determined. Immediately after exercise, group R had the highest level of LA, whereas groups D and J had the lowest levels. A significant increase in plasma leptin concentration was stated only in group H in samples taken immediately after the end of the exercise period and 30 min after the exercise period, as compared with the values obtained at rest. A significant increase in plasma cortisol concentration was found immediately after the end of the exercise period in groups R and H. Leptin exercise-to-rest ratio was significantly correlated with cortisol exercise-to-rest ratio (r=0.64; P<0.001). The increase in plasma leptin concentration in exercised horses was related to the increased plasma cortisol concentration and took place only during long-lasting exercise, which was not intensive.